Dekonstruksi Orientalisme (Telaah atas Pemikiran Leonard Binder) - Muzakki, Akhmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2005)
Ortodox Moslems considered orientalism as a conflict between kafir and mukmin which was sharpened by various tendencies. They appraised, Nurcholis said, because there are three prejudice roots of the West to Islam which caused the emerge of negative stigma that are the prejudices on religious, socio-politic and culture understandings. Or, as stated by Hasan Hanafi, orientalism saw